2022
DOI: 10.1097/opx.0000000000001888
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Lens Design on Corneal Power Distribution in Orthokeratology

Abstract: SIGNIFICANCE: This study will enhance our understanding of the effects of orthokeratology lens design on corneal profile, the results of which may be useful in developing future orthokeratology lens designs.PURPOSE: This study aimed to evaluate the effect of lens design on corneal power distribution after orthokeratology using mathematical methods.METHODS: Sixty-five subjects were enrolled in this prospective study and assigned to four groups: Euclid with 6.2-mm back optic zone diameter (aged <14 years), Eucli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…For example, some studies have investigated the relationship between smaller TZ and greater peripheral power change ( Pauné et al., 2021 ; Zhang et al., 2022 ), suggesting a smaller BOZ leads to a greater peripheral corneal power change. Others have examined the effect on myopia control outcomes of decentration of the TZ ( Chen et al., 2018 ; Gu et al., 2019 ; Wang and Yang, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies have investigated the relationship between smaller TZ and greater peripheral power change ( Pauné et al., 2021 ; Zhang et al., 2022 ), suggesting a smaller BOZ leads to a greater peripheral corneal power change. Others have examined the effect on myopia control outcomes of decentration of the TZ ( Chen et al., 2018 ; Gu et al., 2019 ; Wang and Yang, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Guo et al, 20 Zhang et al, 17 and Paune et al, 24 a smaller treatment zone was obtained by reducing the BOZD of VST orthokeratology, and the results showed that the axial length of patients wearing smaller BOZD lenses grew slower. Zhang et al 35 also found that the smaller treatment zone of VST-designed and CRT-designed orthokeratology can slow down the axial growth of myopic children.…”
Section: Discussionmentioning
confidence: 96%
“…After wearing orthokeratology, a relatively flat area is formed in the center of the front surface of the cornea under the pressure of the lens base curve, which is called the treatment zone. 15 Carracedo et al 16 and Zhang et al 17 showed that wearing the orthokeratology with a smaller back optic zone diameter (BOZD) produced a smaller treatment zone diameter (TZD). The TZD is influenced not only by the design of the lens itself but also by certain biometric factors.…”
mentioning
confidence: 99%
“…3,19,20 Related to this, lens design can influence changes in epithelial thickness because of different sizes of treatment zones and number of lens curves. Zhang et al 21 showed that lenses with a smaller back optic zone diameter yielded a faster myopic reduction and a smaller aspheric treatment zone.…”
Section: Discussionmentioning
confidence: 99%